Las pteridofitas en la historia de las plantas de la Nueva España de Francisco Hernández, protomédico español - Riba, Ramón; Pérez-García, Blanca; Orozco Segovia, Alma (Instituto de Ecología, A.C., 1993)
Francisco Hernández (1517/1518-1584), in his Historia de las Plantas de la Nueva España, included 3076 piants with native  names, descriptions, medicinal uses and región where they grow. Fifty two of them have been identified as fems but  unfortunately only five are illustrated, Previous studies of the  books of Hernández were made by F. Altamirano, M.  Altamirano, M. A. Batalla et al., F. Miranda and J. Vaidés, F.  Miranda et al., and J. Vaidés and H. Flores, who attempted the  botanical interpretaron of the piants with partial success,  because of the vagueness of the descriptions. Based on the  former interpretations, a new evaluation of the pteridophytes  included in Hernández is presented. We believe that five piants  of the fifty two pteridophytes mentioned are angiosperms (2  Ranunculaceae, 1 Piperaceae, 1 Leguminosas or Coriariaceae  and 1 of unknown family); the ¡nterpretation of twelve piants is  noí possible, although apparently they are pteridophytes. The  remaining 35 plants can be interpreted as pteridophytes, at  least at the genus level.